Toward Evidence-Based Practice. Issue 4 (July 2021) - Rohan, Annie; Breman, Rachel Blankstein; Capitulo, Kathleen Leask; Abel, Nancy O'Brien
Abstract : Experts suggest how 6 research articles can be used in nursing practice.